Integration of Athletics and Academics - John Spicer Nichols; Thomas F. Corrigan; Marie Hardin (University of Kansas Libraries, 2011)
The Coalition on Intercollegiate Athletics (COIA), an alliance of 57 university faculty senates, was founded in 2002 to provide a faculty voice in the national discussion about how to best maintain academic integrity in big-time college sports. COIA's most recent white paper, Framing the Future: Reforming Intercollegiate Athletics (2007), proposes best practices for individual universities to help ensure that college sports are more fully integrated into their academic goals, values and missions. Reported here are the results of a national survey that gauged the extent to which COIA's best practices have been adopted by schools participating in the Football Bowl Subdivision. The findings suggest that big-time athletics programs have a number of underutilized tools at their disposal that can assist them in protecting core academic values and standards at universities competing at the highest level of intercollegiate sport.